The Number of Mushafs Attributed to The Caliph Uthman - Hasankhon Abdumajidov (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
The article examines the number of Mushaf of Uthman and the countries to which they were sent. It also surveys on the sources on a relevant topic and provides conclusions drawn